Kurikulum pendidikan islam dalam perspektif al quran dan al hadits di sman plus sukowono - Angga Sofyan; Syamsul Anam; Faisol Nasar Bin Madli (Sahabat Publikasi, 2023)
The term curriculum comes from Greek, meaning place of racing. This term is taken from the world of sports in ancient Rome, Greece. Contains the meaning of a distance that must be traveled by runners from star to finish. The term curriculum entered education in 1955 with the meaning of a number of subjects in one agency. This study aims to find out how the implementation of the educational curriculum in the perspective of the Quran and Hadith at SMAN PLUS Sukowowno, will it run relevant to the curriculum theory contained in it with the actual conditions in daily life at school The approach used in this study is a qualitative descriptive approach, namely the Miles and Huberman theory, researchers use this theory because of the data analysis process carried out by researchers at the time of data collection after data collection research. The principles contained in SMAN Plus Sukowono include six aspects, the first of which is the Activity Principle, Motivation Principle, Individual Principle, Environmental Principle, Concentration Principle and Game Principle. Of these six aspects, the journey is not as smooth as what he designed, there are still obstacles or problems both internal and external